대학의 비교과 활동 촉진을 위한 디자인씽킹 체크리스트 개발과 운영사례 - 조성희(Cho, Sunghee); 임이랑(Lim, IRang); 김주연(Kim, Jooyeon); 김연희(Kim, Yeonhee); 김한나(Kim, Han Na) (교양교육연구, 2021)
본 연구의 목적은 대학에서의 비교과 활동 촉진을 위한 디자인씽킹 기반 학습자용 체크리스트를개발하고, 이를 활용한 창의설계 비교과 프로그램 운영사례를 통해 그 효과성을 검증하는 것이다. 이를 위해 선행연구에 근거하여 체크리스트 초기문항을 도출하였고, 15명의 전문가 패널을 대상으로델파이 조사를 실시하여 내용 타당도를 검증하였다. 델파이 분석결과, 디자인씽킹 5단계에 따라 공감3문항, 문제정의 6문항, 아이디어 도출 5문항, 프로토타입 3문항, 테스트 5문항으로 총 22개 문항이도출되었다. 최종 도출된 체크리스트의 효과성을 검증하고자 이를 디자인씽킹 기반 비교과프로그램에적용하고, 89명의 대학생을 대상으로 수집된 자료를 분석하였다. 그 결과, 문제해결능력의 하위영역중 ‘문제명료화’와 ‘계획실행’에서 유의미한 향상을 보였다. 본 연구에서 개발된 대상별 체크리스트와디자인씽킹 기반 비교과 프로그램 적용사례는 학습자가 디자인씽킹 과정을 비교과 활동에 보다 적극적으로 적용하는데 있어서 유용하게 활용될 수 있을 것으로 기대된다. The purposes of this study were to develop a checklist, which guides the process of design thinking for the students, and to analyze the case of A university, so as to facilitate the non-subject educational activities in university. From the results of the literature review, we derived the preliminary items included in the checklist. After verifying the content validity, a Delphi survey by 15 experts was conducted. Corresponding to the five steps of design thinking, a total of 22 items, including 3 items for ‘empathize’, 6 items for ‘define’, 5 items for ‘idea’, 3 items for ‘prototype’, and 5 items for ‘test’ were finally selected for the students’ checklist. With regard to their problem solving abilities, the design thinking based program might be beneficial for enhancing students’ competence when it comes to problem clarification and plan execution. Furthermore, the developed design thinking checklists, along with the presented case of the design thinking program, are expected to encourage students to more actively apply the design thinking process to their non-subject educational activities. KCI Citation Count: 0